Lorentz-symmetry test at Planck-scale suppression with a spin-polarized 133 Cs cold atom clock - Bars, H Pihan-Le (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2018)
We present the results of a Local Lorentz Invariance (LLI) test performed with the 133Cs cold atom clock FO2 [1], hosted at SYRTE. Such test, relating the frequency shift between 133Cs hyperfine Zeeman substates to the Lorentz violating coefficients of the Standard Model Extension (SME), has already been realized in [2] and led to state-of-the-art constraints on several SME proton coefficients. In this second analysis we used an improved model, based on a second order Lorentz transformation and a SCRMF nuclear model, which enables us to extend the scope of the analysis from purely proton to both proton and neutron coefficients. We have also become sensitive to the isotropic coefficient ~cTT, another SME coefficient that was not constrained in [2]. The resulting limits on SME coefficients improve by up to 13 orders of magnitude the present maximal sensitivities for laboratory tests and reach the generally expected suppression scales at which signatures of Lorentz violation could appear [3]